ANALISIS RASIO KECUKUPAN MODAL KERJA PADA PT PERKEBUNAN MITRA OGAN - Sally Maria Bramana (Jurnal Ilmiah Ekonomi Global Masa Kini)
Sally MB, Working capital is very important for every company, because almost all companies require working capital to finance the daily operasinal activities. The company is required to always improve the efficiency of its work so as to achieve the objectives expected by the company to achieve optimal profit. Without sufficient working capital, the activities of a company's operations can not run smoothly. This study aims to find out how the working capital adequacy ratio. This research was conducted at PT Perkebunan Mitra Ogan. The data used are secondary data in the form of financial statements of PT Perkebunan Mitra Ogan. Where the results of the analysis of the working capital adequacy ratio at the company will provide an overview of how the company can manage its working capital well. If the company can use the working capital properly, it will be obtained sufficient capital. Conversely, if the company experiencing a shortage or decrease in working capital, will encourage the company to experience credit in banks or other outside parties and can hamper the smooth operation of the business.Keywords: Working Capital Management Company, Capital Adequacy RatioWork